A brief review on optical properties of planar metallic interfaces and films: from classical view to quantum description. (4th October 2021) - Krasavin, Alexey V
Abstract: With the rapid development of nanophotonics, metals play an ever increasing role in modern optics. At the same time, optical properties of metals are more complex than it is usually assumed in basic models. Such behaviour leads to intriguing phenomena at the nanoscale and also has a profound impact on conventional optical effects. In this brief topical review basic concepts and approaches for the description of an optical response of metals will be overviewed for the case of planar metallic interfaces and films, with an aim to provide a complete and inter-related prospective and also give a general guidance on the level of description needed to treat an optical system at hand.